2020
DOI: 10.21037/jtd-20-2073
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of clinical response to omalizumab in moderate-to-severe asthma patients using the change in total serum IgE level

Abstract: Background: Omalizumab (OMA) is an effective anti-immunoglobulin E (IgE) treatment for moderateto-severe asthma. However, predicting an individual's response is difficult. Monitoring change of total serum IgE may be useful for predicting the response to OMA. The purpose of this study was to determine if measuring the change in total IgE level could predict the response to OMA in patients with moderate-tosevere asthma. Methods: This study included 25 patients (11 females and 14 males; mean age =46.1 years; mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Tajiri et al 18 found that serum-free IgE levels during the follow-up for omalizumab treatment may have predicted the response to omalizumab in their prospective observational study. In addition, Li et al 19 showed that the changes in total serum IgE levels may help evaluate responses to omalizumab treatment. Naumova et al 31 provided evidence that measuring cumulative levels of IgE specific for respiratory allergens serve as biomarker to enhance the success of IgE-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tajiri et al 18 found that serum-free IgE levels during the follow-up for omalizumab treatment may have predicted the response to omalizumab in their prospective observational study. In addition, Li et al 19 showed that the changes in total serum IgE levels may help evaluate responses to omalizumab treatment. Naumova et al 31 provided evidence that measuring cumulative levels of IgE specific for respiratory allergens serve as biomarker to enhance the success of IgE-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that Galectin-3, 13 , 14 serum periostin, 15 baseline serum chemokine interferon-γ inducible protein 10 kDa (CXCL10), interleukin (IL)-12, 16 and IL-13 in induced sputum supernatants 17 may be biomarkers for predicting the response to omalizumab treatment. Serum-free immunoglobulin E (IgE) levels 18 and changes in total serum IgE 19 during follow-up can also be used as biomarkers for omalizumab treatment; however, it is not easy to detect free IgE clinically. The literature reported that fractional exhaled nitric oxide (FeNO), blood eosinophil count, and forced expiratory volume in 1 s (FEV1) are clinical indicators for responsiveness to omalizumab.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, OCS dosage, number of acute exacerbations and changes in ACT scores as well as pulmonary function FEV 1 and PEF were used to assess e cacy. The ACT score was used as the evaluation criterion in this study, and patients with an improvement in ACT score up to a MID score of 3 after treatment39 or with a poor or very poor level of control before treatment (ACT score 5-19) were de ned as responding after treatment with good asthma control (ACT score [20][21][22][23][24][25]. This de nition re ects the improved level of asthma control and correlation analysis has shown that it also better re ects the reduction in OCS use and the number of acute exacerbations, which has been used in some previous studies [15,39].…”
Section: Discussionmentioning
confidence: 99%
“…Total IgE levels at this time do not re ect free IgE levels and therefore it is not recommended to evaluate the effect of treatment based on changes in total serum IgE levels after treatment [19,20]. Studies [21,22] to measure the diagnostic predictive value of free IgE levels for the e cacy of omalizumab are therefore ongoing, but are currently sparse and the results suggest that they cannot be used to predict and assess treatment e cacy. However, a number of studies [23,24] suggest that administration of omalizumab therapy by total serum IgE levels is a reliable approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanisms have not been reported, dupilumab is thought to function as a dual receptor antagonist of the type I and type II IL-4R complexes, by inhibiting their biological actions [36,37]. •Airway remodeling [38] •Specific IgE antibody positivity or skin prick test [39] •Increase of serum IgE at 4 week [40] •High eosinophils (blood) [41] •High FeNO [41] •Decrease exacerbationrate [42] and FeNO [41] •Increase FEV1 and ACQ [43] •Reduce OCS [43] IL-5…”
Section: Therapeutic Antibodies For Bronchial Asthmamentioning
confidence: 99%